Institutions and Democracy in Russia (a critical view) - Oleinik, Anton (Papeles del Este, 2008)
The relationship between democracy – operationalized through (i) competitive elections, (ii) the rule of law and (iii) the legitimacy of the law in terms of its correspondence to everyday practices – and stability of socio-economic development – operationalized through volatility of annual GDP growth rates – is explored. Fullfledged democracy appears associated with more steady development. Several “democratic stabilizers”, including policies of risk-sharing, are discussed. An in-depth case study of a non-democratic institutional arrangement in Russia suggests that rapid economic growth observed in this country since 1999 may not be stable in the middle- and long run. Both quantitative (the Freedom House, the World Bank and the US Agency for International Development datasets) and qualitative (interviews with Russian state officials) data covering the period from 1995 to 2005 are used in the analysis.